A Laboratory Approach to Study Dust Generation Due to Regrinding - A. W. Khair; Danqing Xu (The National Institute for Occupational Safety and Health (NIOSH), 1992)
"This paper presents a laboratory simulation of regrinding and resulting dust generation. An Automated Rotary Coal Cutting Simulator (ARCCS) was modified to conduct regrinding experiment. In order to estimate the effects of coal properties and operating parameters on regrinding and dust generation, an orthogonal fractional factorial experimental design was implemented in regrinding experiment. Marple personal cascade impactors, Series 290, were used to measure dust concentration during experiment. Three types of coal seams, namely, Waynesburg, Pittsburgh, and Lower Kittanning, were used to represent different coal properties. Experimental results and complete parametric analysis were presented.In a rotary cutting system, all the broken coal and part of the remaining coal from previous cutting cycles must be transported through part or entire circumference of the cutting drum. This transportation of already recovered coal through the cutting zone of rotary head makes it a rotary grinder. Some of the coal particles will be subjected to secondary fragmentation or regrinding in the process. The potential effect on dust generation by regrinding is significant because the cutting head utilizes kinetic energy to comminute recov¬ered coal material. The moving bits and bit blocks on the cutting head impact coal particles and transfer some of their kinetic energy to the particles. After obtaining kinetic energy, coal particles are free to impact one another and they also impact the coal seam or cutting head. During impact, high impact force and high internal stress concentration are created in the particles. Kinetic energy is transformed into strain energy. When stored strain energy exceeds allowable strain energy, the particles will break. A great amount of respirable dust will be generated due to impact failure. In reality, regrinding occurs at the same time as primary cutting. The particles to be ground are the result of primary cutting. Both primary cutting and regrinding produce dust. Therefore, it is impossible to separate regrinding from primary cutting. In order to study respirable dust generation by regrinding and analyze the influencing parameters, a laboratory approach was adopted. In this approach, it is possible to study the regrinding separating from primary cutting."